2011
DOI: 10.1002/app.33616
|View full text |Cite
|
Sign up to set email alerts
|

New method for estimating the extent of curing of thermosetting prepregs

Abstract: Here, we propose a new method for estimating the extent of curing of thermosetting prepregs. In the proposed method, the extent of curing is estimated with the curing index (C i ), defined as the ratio of the glasstransition temperature (T g ) to the ultimate glass-transition temperature of the material. The advantages of this new method over the conventional degree of conversion (a) for estimating the extent of curing of thermosetting prepregs are discussed in detail. C i and a of a toughened epoxy prepreg (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that the final DOC and T g are predominantly affected by curing temperatures . According to DiBenedetto, the DOC and T g have a strong interrelationship: T g increases proportionally with the DOC.…”
Section: Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the final DOC and T g are predominantly affected by curing temperatures . According to DiBenedetto, the DOC and T g have a strong interrelationship: T g increases proportionally with the DOC.…”
Section: Correlationsmentioning
confidence: 99%
“…The T g ‐DOC relationship obtained in this study is slightly different than the one obtained in a previous study. Sabzevari et al showed experimental results for a nonlinear T g ‐DOC relationship and DiBenedetto model for a wide range of DOC and T g . However, the T g ‐DOC relationship in Sabzevari's study for DOC ranging from 0.35 to 0.83 shows an almost linear fit, as also obtained in this study.…”
Section: Correlationsmentioning
confidence: 99%
“…Figure 1. Effects of postcure temperature on glass-transition temperature of resin matrix T g is dominantly affected by curing temperature [23][24][25] . There is a significant dependence of the T g on the molecular weight of the polymer.…”
Section: Resultsmentioning
confidence: 99%
“…18 Since T g mark a physical change in state of the material, it can be accurately determined by either dynamic mechanical analyzer (DMA) or encapsulated sample rheometer (ESR). Similar to degree of cure, glass transition temperature is an important parameter in defining the state of cure.…”
Section: Cure Cyclesmentioning
confidence: 99%
“…Similar to degree of cure, glass transition temperature is an important parameter in defining the state of cure. 18 Since T g mark a physical change in state of the material, it can be accurately determined by either dynamic mechanical analyzer (DMA) or encapsulated sample rheometer (ESR). In this work, to correlate glass transition temperature with the mechanical properties, DMA was used to determine the T g using three point bending clamp according to ASTM D7028-07.…”
Section: Cure Cyclesmentioning
confidence: 99%